Implikasi Hukum Status Tersangka Terhadap Hak Klaim Asuransi - Gatra Sandhitya Kurnia Putra; Ernu Widodo; Moh. Taufik (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
In the context of Indonesian law, the status of a suspect in a criminal case can have significant legal implications, including regarding insurance claim rights. In many cases, individuals who are suspects in criminal cases often face difficulties in obtaining the insurance claims they submit, whether related to life insurance, accident insurance, or other types of insurance. This article aims to examine how suspect status can affect a person's insurance claim rights, as well as how legal rules and insurance practices in Indonesia regulate claim rights in this case. This research uses a descriptive qualitative approach with literature study methods and in-depth interviews with legal practitioners, insurance experts, and parties involved in the insurance claims process. The research results show that although in many cases insurance claims are not automatically rejected due to suspect status, there are administrative procedures that often limit claim rights, as well as the potential for legal discrimination in insurance practices.